9q-5q+4q-6q-2=14

Simple and best practice solution for 9q-5q+4q-6q-2=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9q-5q+4q-6q-2=14 equation:


Simplifying
9q + -5q + 4q + -6q + -2 = 14

Reorder the terms:
-2 + 9q + -5q + 4q + -6q = 14

Combine like terms: 9q + -5q = 4q
-2 + 4q + 4q + -6q = 14

Combine like terms: 4q + 4q = 8q
-2 + 8q + -6q = 14

Combine like terms: 8q + -6q = 2q
-2 + 2q = 14

Solving
-2 + 2q = 14

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 2q = 14 + 2

Combine like terms: -2 + 2 = 0
0 + 2q = 14 + 2
2q = 14 + 2

Combine like terms: 14 + 2 = 16
2q = 16

Divide each side by '2'.
q = 8

Simplifying
q = 8

See similar equations:

| -4x^2-32x-48=0 | | (-3x-4y)(9x^2-12xy+16y^2)= | | I=1000-40(7) | | -2(3x+5)-2x=x-43 | | -4/11x=8/99 | | 2.25x+5=13.5t+14 | | 252=(4+y)16.8 | | 4(x+2)=4(x+13) | | -8x+36= | | n+n+2+n+4=-78 | | 44t+t-49t-t+6t=6 | | 5x-70=3x-90 | | 54=1/6w | | -6=d/3 | | Y=-7/3x-4 | | 1/6w=54 | | 9.3=31n | | 1+2=2+7 | | 0=2x^4-4x^2-48 | | X=7/3y-4 | | 3a+21=4a-60 | | 23n+5n-24n-4n+10n-3=17 | | I=1000-40r | | 10/8=8x/10 | | -2(x-6)/7=35 | | 2y=3x+21 | | 90=22.50c | | y=2x^4-4x^2-48 | | 1/3x-9=8 | | -52=4z | | 3k-74=2k-8 | | -9+5(6h-3)= |

Equations solver categories